Caracterização molecular dos rearranjos gênicos de imunoglobulinas e receptores de células T em pacientes com leucemia linfoide aguda - Leal, Isabel Agne Souza (2016)
Acute Lymphocitic Leukemia (ALL) is the most common cause of childhood cancer and occurs in adults in 20%. Lymphoblasts accumulation is a characteristic of the disease since the leukemic cells retain some multiplication ability without differentiation. The chemotherapy treatment for ALL has been proven effectiveness leading 95% cases to remission however, some patients may have recurrence disease. An accurate diagnosis is critical for the correct treatment and therefore longer survival. Molecular biology techniques have contributed to the early detection of recurrence, mainly by PCR method. Considering the high frequency of clonal rearrangements in leukemia (about 90 to 95%) the analysis of clonal immunoglobulin (Ig) or T-cell receptor (TCR) rearrangements by PCR has been shown to be useful for treatment monitoring the minimal residual disease. This study aimed to standardize the PCR for Ig and TCR rearrangements technique and characterize the pacients at the University Hospital of Santa Maria, through these analysis. After adjustments the technique was considered a reliable procedure and relatively easy to perform. The higher frequency of rearrangements were detected in IgH gene (82.76%) by the DH7 sequences (14 samples), Vg1 (10 samples), VH3 and V2D3 (9 cases). IgK rearrangements occurred in frequency of 31.03, TCRG and TCRD rearrangements to 41.37%, and Sil-Tal to 3.45%.